Education Package Reduce Physical and Psychological Complaint In Cervical Cancer Patient with Chemotherapy - Mira Triharini (Universitas Airlangga, 2009)
Introduction : Patient with cervix cancer who receives chemotherapy experience problems in physical or psychological. Physical complaints such as nausea, vomiting and fatigue. Psychological responses such as anxiety and depression can be reduced by providing education about the care package for themselves at home. The education package at the gynecology ward RSU Dr. Soetomo Surabaya has been developed which contains about nutrition, activity, psychological aspects and progressive muscle relaxation exercise. The objective of this study explore the relationship of the educational package with physical and psychological complaints of cervical cancer patients with chemotherapy.Methods : This research use cross-sectional design. The sampling technique used total population. The sample was taken from those suitable with inclusion criteria, with the total sample 25 patients. Data were collected by using a questionnaire. Data analysis using the T test and chi-squere.Results : Results showed that there are differences level of nausea, vomiting, fatigue and the entry psychological response to the respondents before and after intervention (p<0.05). The results showed that there is relationship between age with anxiety (p=0,032), relationship between the status of work with fatigue (p=0,003) and relationship between the frequency of chemotherapy with fatigue (p=0,015).Conclusion : It can be concluded that education package can reduce physical and psychological complaint in serviks cancer patient with chemoteraphy. Discussion : Implications the results of this research is the educational package can be developed as part of the nursing care of cervical cancer patients with chemotherapy to reduce physical and psychological complaints.